Fabrication of bifunctional nanocomposite for dye degradation. Issue 3 (15th February 2020) - Khalid, W.; Abbasi, M.A.; Ullah, F.; Atif, M.; Ali, Z.; Nadeem, K.; Farooq, U.; Amin, F.
Abstract: An effective photocatalytic system is designed to treat with methylene blue. Graphene oxide matrix was decorated with cobalt ferrite and zinc oxide nanoparticles, providing it with dual functionality. The nanocomposite was prepared via sonochemistry. Structural characterization was done by X-ray diffraction. Morphology was observed by scanning electron microscopy while elemental analysis confirmed the purity of the synthesized nanocomposite. The photocatalytic activity of nanocomposite was tested for denaturing methylene blue under solar conditions. Enhanced photocatalytic activity was observed due to trapped electron-hole pairs at graphene oxide surface and other interfaces of the nanocomposite. The efficiency of photocatalyst was calculated as 98% within 15 min which was further examined till 5 more repeated cycles.